On the Riesz summability of the eigenfunction expansions on a closed domain - Rakhimov, Abdumalik; Saydatomov, Erkin; Sheraliev, Shuhrat (Faculty of Sciences and Mathematics, University of Nis, Serbia, 2019)
In the present paper we study the Riesz summability on a closed domain expansions in eigenfunctions of the first boundary value problem for the Schrodinger operator with a weak singular potential.